A prospective observational study to investigate the correlation analysis between neonatal hyperbilirubinemia and deafness gene: Study protocol clinical trial (SPIRIT compliant). Issue 17 (April 2020) - Wu, Xiaohui; Gao, Xingqiang; Li, Gang; Cao, Qiuxue; Guo, Yufeng; Deng, Haiyan; Zheng, Yun
Abstract: Introduction: There are many studies on the relationship between serum levels of hyperbilirubinemia and hearing impairment. However, the mechanism of hyperbilirubinemia on auditory impairment is not clear. Methods and analysis: A total of 1000 children with hyperbilirubinemia who are mainly indirectly elevated bilirubin in the full-term neonatal ward of Xiamen Children's Hospital from March 2020 to September 2020 will be enrolled. Using second-generation high-throughput sequencing technology, 127 deaf-related genes were sequenced from the collected samples. At the same time, physical audiometry was performed on the selected persons and audiometry data were recorded. Discussion: In this study, we will combine gene sequencing with clinical indications of hyperbilirubinemia to find the loci suitable for high-frequency pathogenic deafness related to hyperbilirubinemia, so as to provide early guidance for deafness gene screening in children with hyperbilirubinemia. Trial registration: Chinese Clinical trial registry: ChiCTR2000030075.